THE BASIC COMPETENCES CAN BE DEVELOPED THROUGH THE DUAL MODALITY IN A HIGH VULNERABILITY PROFESSIONAL TECHNICAL LICENSE - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2021)
In the context of Professional Technical Education, Dual Modality has been a commitment of the Chilean Ministry of Education to improve Professional Technical training in High School. The change has involved a curricular innovation around the development of basic competences where, in addition to the teacher and the traditional classroom, other agents and other scenarios that share the work of teaching concur. In this context, the research consigned, according to its objectives and methodological formulation, describes the characteristics of the Dual Professional Technical training of the Administration specialty of the Monseñor Guillermo Carlos Hartl Educational Complex of the Pitrufquén commune , in Chile . It is intended to investigate the effectiveness of the integrated curriculum through the assessment of achievement of the basic competencies of students who are in the 4th Middle Year of said specialty (with Dual mode), in direct relation to the required graduate and professional profile and in contrast, with that of students of the specialty of "Electricity", without the Dual Modality.